Prevalence of adenocarcinoma of the oesophagus in two teaching hospitals in Gauteng Province, South Africa. - Singh Kiyasha (My University, 2018)
Introduction: Oesophageal carcinoma is the eighth most common cancer worldwide and the sixth most common cause of cancer-related mortality. The incidence varies markedly between race, age, and geographic region, environmental and nutritional factors. In western populations, carcinoma of the oesophagus is uncommon whereas endemic areas include China, India, Iran, Russia and South Africa. The incidence of oesophageal adenocarcinoma has rapidly risen over the past decades however squamous cell carcinoma of the oesophagus remains the most common worldwide. The prevalence of oesophageal carcinoma is high in South Africa and contributes significantly to the burden of the disease. These carcinomas remain asymptomatic during much of their development and once diagnosed are usually at an advanced stage. Hence identifying carcinogens and reducing exposure to risk factors such as smoking and alcohol, through education together with early detection methods can significantly reduce this burden. This study is aimed at evaluating the cases of oesophageal carcinoma currently presented to our institutions. Aim(s): -To examine the demography and prevalence of adenocarcinoma of the oesophagus in patients presenting to academic hospitals of the University of Witwatersrand. -To compare the number of patients with adenocarcinoma (AC) of the oesophagus and squamous cell carcinoma (SCC) of the oesophagus. -To list the number of patients with adenocarcinoma of the oesophagus who underwent resection. -To determine how often concomitant Barrett's metaplasia is present in the resected specimen. Methods: This is a retrospective study of all the cases of oesophageal malignancy recorded on the NHLS database at CMJAH and CHBAH from 0 1/0tn 00I- 31/1 2/2013. Demographic variables including age, gender and population group where noted were recorded. Results: The prevalence of oesophageal carcinoma in our two teaching hospitals was on a downward trend. There was a significant decrease noted in the SCC subtype. The AC subtype prevalence was on an upward trend. The results we experienced were consistent with worldwide trends. Conclusion: The prevalence of oesophageal carcinoma in these two teaching hospitals showed a downward trend. This was due to the significant decrease noted in the SCC subtype, AC was still uncommon but the prevalence of the AC subtype appears to be on an upward trend. The results of this study were consistent with worldwide trends.
Dissertation submitted for the Degree of Master in Medicine at the University of the Witwatersrand, Johannesburg.